A directed approach for the identification of transcripts harbouring the spliced leader sequence and the effect of trans-splicing knockdown in Schistosoma mansoni - Marina de Moraes Mourao; Maina Bitar; Francisco Pereira Lobo; Ana Paula Peconick; Priscila Grynberg; Francisco Prosdocimi; Michael Waisberg; Gustavo Coutinho Cerqueira; Andrea Mara Macedo; Carlos Renato Machado; Timothy Yoshino; Gloria Regina Franco (Memorias do Instituto Oswaldo Cruz, 2013)
Schistosomiasis is a major neglected tropical disease caused by trematodes from the genus Schistosoma. Because schistosomes exhibit a complex life cycle and numerous mechanisms for regulating gene expression, it is believed that spliced leader (SL) trans-splicing could play an important role in the biology of these parasites. The purpose of this study was to investigate the function of trans-splicing in Schistosoma mansoni through analysis of genes that may be regulated by this mechanism and via silencing SL-containing transcripts through RNA interference. Here, we report our analysis of SL transcript-enriched cDNA libraries from different S. mansoni life stages. Our results show that the trans-splicing mechanism is apparently not associated with specific genes, subcellular localisations or life stages. In cross-species comparisons, even though the sets of genes that are subject to SL trans-splicing regulation appear to differ between organisms, several commonly shared orthologues were observed. Knockdown of trans-spliced transcripts in sporocysts resulted in a systemic reduction of the expression levels of all tested trans-spliced transcripts; however, the only phenotypic effect observed was diminished larval size. Further studies involving the findings from this work will provide new insights into the role of trans-splicing in the biology of S. mansoni and other organisms. All Expressed Sequence Tags generated in this study were submitted to dbEST as five different libraries. The accessions for each library and for the individual sequences are as follows: (i) adult worms of mixed sexes (LIBEST_027999: JZ139310 - JZ139779), (ii) female adult worms (LIBEST_028000: JZ139780 - JZ140379), (iii) male adult worms (LIBEST_028001: JZ140380 - JZ141002), (iv) eggs (LIBEST_028002: JZ141003 - JZ141497) and (v) schistosomula (LIBEST_028003: JZ141498 - JZ141974).